Предмет: Алгебра,
автор: artur7777777777
(х – 3)(х + 1) + (х + 5)(х – 5)= 4 – 2х
Ответы
Автор ответа:
0
Ответ:
х=1/3
Объяснение:
(х-3)(х+1)+(х+5)(х-5)=4-2х
2х-х+3х-х=4+2-5
3х=1
х=1/3
Автор ответа:
0
Ответ:
Х1=-4; х2=4
Объяснение:
Х^2+х-3х-3+х^2-25=4-2х
2х^2-2х-28=4-2х
2х^2-28=4
2х^2=4+28
2х^2=32
х^2=16
х1=4
х2=-4
Похожие вопросы
Предмет: Английский язык,
автор: Лерка1711
Предмет: Английский язык,
автор: natasha050788
Предмет: Другие предметы,
автор: DIIIana
Предмет: Алгебра,
автор: знания2021
Предмет: Литература,
автор: kafeeva67